ASGARD+: A New Modular Platform for Bacterial Antibiotic-Resistant Analysis - Montero Vargas, Maripaz (2023)
ASGARD+ (Accelerated Sequential Genome-analysis and Antibiotic Re- sistance Detection) is a command-line platform for automatic identification of antibiotic-resistance genes in bacterial genomes, providing an easy-to-use interface to process big batches of sequence files from whole genome se- quencing, with minimal configuration. It also provides a CPU-optimization algorithm that reduces the processing time. This tool consists of two main pro- tocols. The first one, ASGARD, is based on the identification and annotation of antimicrobial resistance elements directly from the short reads using different public databases. SAGA, enables the alignment, indexing, and mapping of whole-genome samples against a reference genome for the detection and call of variants, as well as the visualization of the results through the construction of a tree of SNPs. The application of both protocols is performed using just one short command and one configuration file based on JSON syntax, which modulates each pipeline step, allowing the user to do as many interventions as needed on the different software tools that are adapted to the pipeline. The modular ASGARD+ allows researchers with little experience in bioinfor- matic analysis and command-line use to quickly explore bacterial genomes in depth, optimizing analysis times and obtaining accurate results. © 2023 Wiley Periodicals LLC.